KERAGAMAN PENGADUAN LAYANAN PUBLIK DI KALIMATAN SELATAN MELALUI APLIKASI SP4N LAPOR! - Hilarion Hamjen; Rachma Ainun Nikmah (Universitas Lambung Mangkurat, 2020)
Regulation of Ministry of Empowerment of State Apparatus and Bureaucratic No. 3 year 2015 mandates the implementation of technology-based national public complaints management and each region integrated by the Lapor ! SP4N application include in South Kalimantan. The Sp4N lapor ! application is used to make complaints related to public service issues. However there is no research about the diversity of public service complaints by Lapor application in South Kalimantan. In order that this research was conducted which aims to find out the diversity of complaints by Lapor application in South Kalimantan. This study uses a quantitative approach supported by qualitative using saturated sampling techniques to the Lapor aplication users who are willing to be surveyed in April 2018 in Banjarmasin City, Banjarbaru City, Banjar District and South Kalimantan Province. The results showed that in Banjarmasin City, Banjarbaru and Banjar District had similarities in terms of the variety of reports that were reported with frequencies of 1 to 2 reports and the reported problems that were mostly reported were quite diverse but the most dominant was reports is related to the damage of road infrastructure. While the informan education and occupation are quite varied, there are backgrounds from Senior dan junior high school, then entrepreneurs, government employees or policeman or national Army. Public are constrainted when the internet access is slow or unavailable. Another constrain is because they do not understand about the use of the application. As for the public who has already know but reluctant to report because they are afraid of the consequences of reporting, security and comfort is disrupted.